2009
DOI: 10.1038/sj.bjc.6605219
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenesis and lymphangiogenesis are downregulated in primary breast cancer

Abstract: BACKGROUND: Angiogenesis and lymphangiogenesis are considered to play key roles in tumour growth, progression and metastasis. However, targeting tumour angiogenesis in clinical trials showed only modest efficacy. We therefore scrutinised the concept of tumour angiogenesis and lymphangiogenesis by analysing the expression of crucial markers involved in these processes in primary breast cancer. METHODS: We analysed the expression of angiogenic, lymphangiogenic or antiangiogenic factors, their respective receptor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 46 publications
(34 reference statements)
4
15
0
Order By: Relevance
“…This finding is consistent with the previous studies (Faoro et al, 2008) indicating although the generation of intratumoral lymphatic vessels may enhance tumor cell metastasis, this may not be an essential requirement as lymphatic spread can occur using pre-existing vessels (Mandriota et al, 2001). Also, there are previous studies showing lymphangiogenesis is not increased in tumor tissues but is even less activated than in normal breast tissue (Boneberg et al, 2009). This phenomenon was explained by that solid tumors do not have lymphatic vessels, due to the increased interstitial pressure created by the proliferating cancer cells (Pepper, 2001).…”
Section: Discussionsupporting
confidence: 92%
“…This finding is consistent with the previous studies (Faoro et al, 2008) indicating although the generation of intratumoral lymphatic vessels may enhance tumor cell metastasis, this may not be an essential requirement as lymphatic spread can occur using pre-existing vessels (Mandriota et al, 2001). Also, there are previous studies showing lymphangiogenesis is not increased in tumor tissues but is even less activated than in normal breast tissue (Boneberg et al, 2009). This phenomenon was explained by that solid tumors do not have lymphatic vessels, due to the increased interstitial pressure created by the proliferating cancer cells (Pepper, 2001).…”
Section: Discussionsupporting
confidence: 92%
“…However, the therapeutic efficacies have been found to be modest and transitory followed by restoration of neo-angiogenesis and disease progression. Based on these results, subsequent studies conducted have revealed that the resistance towards anti-VEGF therapies is either due to evasive or pre-existing unresponsiveness [28]. Our observations in this study show evidence that knockdown of VEGF-A lead to enhanced expression of VEGF-C and thus this may compensate for some of the functions of VEGF-A.…”
Section: Discussionmentioning
confidence: 51%
“…43 In contrast with the enthusiasm for VEGF-targeted growth factor genes -including VEGF -were greater in adjacent normal tissues than in the primary tumour tissue. 44 The authors concluded that primary breast tumours are not a site of active angiogenesis. The role of pro-and anti-angiogenic factors in metastatic tissues needs to be elucidated.…”
Section: Discussionmentioning
confidence: 99%